Some issues concerning sector concentration. Evidence from Romania - Mărginean, Silvia; Toma, Ramona (Journal of Business Economics and Management, 2011)
This paper examines the dynamics of sector concentration in Romania starting from two basic questions: how concentrated the economic activities are and what factors determine the economic concentration. The lack of availability of concentration ratio series for Romanian economy has limited the research in this field. The paper reports the concentration ratios dynamics in Romania during the period 1996–2004, looking at the differences between industries and offers some possible explanations. We use the simple concentration ratio (CR) for the largest 5 and 20 companies to measure concentration in 25 industries according to the sales figure and the number of employees. Our study has been limited to the processing industry, because the mining industry continues to have a very high level of concentration, without any significant changes in the analysed period; commerce, services and constructions are sectors with low entrance barriers and a strong geographic concentration character, thus their analysis can become irrelevant for the national level. Based on the average values of the concentration coefficients that it was determined for the period 1996–2004 we proposed the map of Romanian industry concentration, as a graphical tool for a synthetic view of the general concentration level in a national economy. Article in English. Valdymo sistema didžiosiose Madeiros salos imonėse: rezultatų apskaitos sistemos naudojimo pavyzdžiu Santrauka. Nagrinejama tam tikru Rumunijos pramones sektoriu koncentracijos dinamika, atsakant i du pagrindinius klausimus: kokia yra ekonominiu veiklu koncentracija ir kokie veiksniai lemia ju pasiskirstym. Taèiau del kai kuriu ekonominiu apribojimu tyrimo metu nebuvo galimybes ivertinti tam tikru aspektu, nuo kuriu ir buvo atsiribota. Straipsnyje pateikiamas pramones sektoriu koncentracijos santykis, apimantis 1996–2004 metu laikotarpi, buvo nustatyti pramones šaku skirtumai ir pateikti komentarai. Autoriai daugiau demesio skiria apdirbamajai pramonei, nes kasybos pramone ir toliau išlieka viena iš labiausiai koncentruotu veiklos rušiu, dideliu pokyèiu tuose pramones sektoriuose analizuojamu laikotarpiu nebuvo pastebeta. Prekybos, aptarnavimo ir paslaugu bei statybos sektoriai turi nedidelius ribojimus, ir geografine koncentracija yra gera, todel ju analize buvo nustatyta kaip nereikšminga. Gauti tyrimo rezultatai naudoti sudarant Rumunijos pramones koncentracijos žemelapi ir nustatant lyginamji svori bendroje nacionalineje ekonomikoje. Reikšminiai žodžiai: koncentracija, koncentracijos santykis, regioninis sektorius, pramone, Rumunija.